Answer:
• (7x-1)(x-3)=0
,
• x=1/7 or 3
Step-by-step explanation:
Given the quadratic equation:
![7x^2-22x+3=0](https://img.qammunity.org/2023/formulas/mathematics/college/pk1v85t1zkmew2tlubjbdmmrduwmbzzazd.png)
First, multiply the first and the last term:
![7x^2*3=21x^2](https://img.qammunity.org/2023/formulas/mathematics/college/vcdhw1bp4x1as5ja4iygqei2ywb6z288wj.png)
Next, find factors of the product above that add up to the middle term:
![-21x-x=-22x](https://img.qammunity.org/2023/formulas/mathematics/college/xg6mssw3u4tdezj1nv41c9stz32gtdt80j.png)
Therefore, we obtain the factored form below:
![\begin{gathered} 7x^2-22x+3=0 \\ \implies7x^2-21x-x+3=0 \\ \implies7x(x^{}-3)-1(x-3)=0 \\ \implies(7x-1)(x^{}-3)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fbb62v5pkbn71ib8vc81i4bjsh8kqg9gro.png)
The equation in factored form is:
![(7x-1)(x^{}-3)=0](https://img.qammunity.org/2023/formulas/mathematics/college/74d8m46ha3y3j20att5bh6dpnzxri43d4t.png)
Next, solve for x:
![\begin{gathered} 7x-1=0\lor x-3=0 \\ 7x=1\lor x=3 \\ x=(1)/(7)\text{ or }x=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fsaw8zcc4zh6hta70uq5hb0a1wcka53kl8.png)
The solution to the equation is x=1/7 or 3.